2023
DOI: 10.1002/advs.202207627
|View full text |Cite
|
Sign up to set email alerts
|

Synergized Tricomponent All‐Inorganics Solid Electrolyte for Highly Stable Solid‐State Li‐Ion Batteries

Abstract: Garnet‐type oxide Li6.4La3Zr1.4Ta0.6O12 (LLZTO) features superior ionic conductivity and good stability toward lithium (Li) metal, but requires high‐temperature sintering (≈1200 °C) that induces high fabrication cost, poor mechanical processability, and high interface resistance. Here, a novel high‐performance tricomponent composite solid electrolyte (CSE) comprising LLZTO−4LiBH4/xLi3BN2H8 is reported, which is prepared by ball milling the LLZTO−4LiBH4 mixture followed by hand milling with Li3BN2H8. Green pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The composite electrolyte delivered 8.02 × 10 –5 S cm –1 of Li + ion conductivity at 30 °C and 0.9999 of ultrahigh Li + transference number, therefore enabling symmetric Li–Li cells 1000 h cycling at 60 °C and 300 h at 30 °C. Further compositing with Li 3 BN 2 H 8 by hand milling and low-temperature heat treatment at 150 °C increased the Li + conductivity to 1.73 × 10 –3 S cm –1 at 30 °C . With LLZTO-4LiBH 4 /5 wt % Li 3 BN 2 H 8 as electrolyte, the Li|Li symmetrical cells stably cycled for 1600 h at 30 °C and 0.15 mA cm –2 , with only ∼30 mV of overpotential.…”
Section: Metal Hydride Superionic Conductorsmentioning
confidence: 99%
“…The composite electrolyte delivered 8.02 × 10 –5 S cm –1 of Li + ion conductivity at 30 °C and 0.9999 of ultrahigh Li + transference number, therefore enabling symmetric Li–Li cells 1000 h cycling at 60 °C and 300 h at 30 °C. Further compositing with Li 3 BN 2 H 8 by hand milling and low-temperature heat treatment at 150 °C increased the Li + conductivity to 1.73 × 10 –3 S cm –1 at 30 °C . With LLZTO-4LiBH 4 /5 wt % Li 3 BN 2 H 8 as electrolyte, the Li|Li symmetrical cells stably cycled for 1600 h at 30 °C and 0.15 mA cm –2 , with only ∼30 mV of overpotential.…”
Section: Metal Hydride Superionic Conductorsmentioning
confidence: 99%
“…Compared with those stable additives with SSEs, some unstable additives also work and exhibit high performance. Xu et al 128 demonstrated a synergized tricomponent composite SSE Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 –4LiBH 4 / x Li 3 BN 2 H 8 , which was prepared by first ball milling Li 6.4 La 3 Zr 1.4 Ta 0.6 O 12 with LiBH 4 and then hand milling with Li 3 BN 2 H 8 . TEM observation displayed a multilayer coating structure.…”
Section: Strategies For Suppressing LI Dendritesmentioning
confidence: 99%